PERBANDINGAN PROFIL GLUKOSA DARAHPADA PASIEN STROKE ISKEMIK DAN STROKE HEMORAGIK DI RSUP FATMAWATI TAHUN 2018 - Intan Rahma Husna (2020)
Stroke is the death of brain cells due to lack of blood flow and oxygen to the brain by blockage or rupture of an artery. Stress hyperglycemia in acute stroke may worsen the clinical outcome and the prognosis of stroke. The purpose of this study is to compare glucose profile between ischemic stroke and hemorrhagic stroke. This is an observational analytic cross-sectional research using consecutive sampling. Data was obtained through medical record period of January-December 2018 in RSUP Fatmawati with each group of stroke consisting of 74 samples. Data was processed using SPSS 2017. Both ischemic stroke and hemorrhagic stroke mostly found in the age above 55 years, with a prevalence of 52 (70,27%) ischemic stroke patients and 44 (59,46%) hemorrhagic stroke patients. Both ischemic stroke and hemorrhagic stroke mostly found in men, with a prevalence of 46 (62,20%) ischemic stroke patients and 42 (56,80%) hemorrhagic stroke patients. Mann-Whitney test shows that there are significant differences of random glucose level (p <0,05), fasting glucose level (p <0,05), 2 hour postprandial glucose level (p <0,05) between ischemic stroke and hemorrhagic stroke, where hemorrhagic stroke has higher random glucose level, fasting glucose level, and 2 hour post-prandial glucose level than ischemic stroke.